Chapter 31: Ethics in digital marketing and social media - Hanlon, Annmarie (SAGE, 2020)
Chapter 31 considers ethics in digital marketing and social media. Whilst digital marketing and social media have disrupted traditional communications, the notion of ethics has been less considered. This chapter presents the emerging ethical issues within this domain, at individual, organisational and societal levels. The chapter starts with an introduction to the data that consumers are willing to share in order to gain access to platforms and explores how ethics has been managed in this domain, highlighting societal approaches to managing the data. It then provides the background to customer data deception and behavioural microtargeting and presents the notion of blurred boundaries, with its potential consequences such as online shaming. Subsequently this chapter looks at harmful online behaviour from trolls to sockpuppets, cyber-bullying to dying for selfies. Moving from risky individual behaviour to that of organisations and the ethical issues of seeking user-generated content, along with the role of influencers. The chapter concludes with a review of the policies and codes of conduct and discusses the future directions of digital and social media marketing ethics as we move towards an open ethics standard.
The SAGE Handbook of Marketing Ethics
Keywords: Digital marketing; social media; ethics; gaining content from customers; user agreements